ABC of Work Related Disorders: OCCUPATIONAL HEARING LOSS AND VIBRATION INDUCED DISORDERS - Jones, C M (BMJ, 1996)
Causes of deafness Sensorineural loss Congenital deafness (associated with maternal rubella or flu or prenatal medication) Familial deafness Birth trauma Childhood illnesses (such as measles (usually bilateral deafness), mumps (unilateral), encephali- tis, meningitis, cerebral abscess, typhus) Ototoxic drugs Streptomycin and some other antibiotics (such as gentamicin and neomycin) Anti-rheumatic drugs Diuretics Quinine, nicotine, alcohol, and aspirin Fracture of base of skull Acoustic neuroma (unilateral deafness) Meniere's disease Presbycusis Conductive loss Impacted earwax Ruptured eardrum (blow to head or explosion) Blockage of eustachian tube Ossicular dysfunction Dislocation Otitis media or fluid Otosclerosis Audiometry Audiometry should be performed when the subject has not been exposed to loud noise for at least 16 hours (or has worn high efficiency muffs before the test). Vascular Neurological * Trauma * Peripheral nerve entrapment * Polyarteritis nodosa * Trauma to arm or neck * Scleroderma * Peripheral neuropathy * Thoracic outlet syndrome * Drugs and other toxic effects * Cold agglutinins * Syringomyelia * Systemic lupus erythematosus * Spinal cord compression * Dermatomyositis * Multiple sclerosis * Rheumatoid arthritis - Prognosis The vascular component can slowly improve if exposure to vibration is stopped early in stage 2, and a change of job should be encouraged.